The Complex Dynamics of Hepatitis B Infected Individuals with Optimal Control - Din, Anwarud; Li, Yongjin; Shah, Murad Ali (Journal of systems science and complexity, 2021)
This paper proposes various stages of the hepatitis B virus (HBV) besides its transmissibility and nonlinear incidence rate to develop an epidemic model. The authors plan the model, and then prove some basic results for the well-posedness in term of boundedness and positivity. Moreover, the authors find the threshold parameter R 0 , called the basic/effective reproductive number and carry out local sensitive analysis. Furthermore, the authors examine stability and hence condition for stability in terms of R 0 . By using sensitivity analysis, the authors formulate a control problem in order to eradicate HBV from the population and proved that the control problem actually exists. The complete characterization of the optimum system was achieved by using the 4 th -order Runge-Kutta procedure.